2012
DOI: 10.1055/s-0032-1304598
|View full text |Cite
|
Sign up to set email alerts
|

Seronegative Myasthenia Gravis and Graves’ Disease. Is there a link?

Abstract: Graves' disease (GD) and myasthenia gravis (MG) are common autoimmune diseases but their coexistence is very rare. They may possibly share the same pathogenetic mechanisms. Recent research has shown the involvement of autoantibodies, lymphocytes, cytokines and chemokines in the pathogenesis of MG and GD. It appears that Th17 cell lineage is involved in autoimmune thyroid disease (AITD) and seems to be key factor in the development of both MG and GD.A 34-year-old male with seronegative myasthenia gravis due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Cases showing equivocal negative results except MG included ischemic oculomotor nerve palsy with ptosis and thyroid associated ophthalmopathy. As ptosis is rare in thyroid associated ophthalmopathy and MG is more frequent in patients with thyroid disease [ 25 , 26 ], an equivocal negative result of the ice test may imply a ‘possible MG’ even if other test results are all negative for MG, and close observation for the symptoms of MG would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Cases showing equivocal negative results except MG included ischemic oculomotor nerve palsy with ptosis and thyroid associated ophthalmopathy. As ptosis is rare in thyroid associated ophthalmopathy and MG is more frequent in patients with thyroid disease [ 25 , 26 ], an equivocal negative result of the ice test may imply a ‘possible MG’ even if other test results are all negative for MG, and close observation for the symptoms of MG would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The association between the two diseases seems to be attributable to autoimmune mechanisms rather than simply by chance. Recent research has shown the involvement of autoantibodies, lymphocytes, cytokines, and chemokines in the pathogenesis of MG [ 17 ]. Thus, seropositive OMG may have a higher prevalence of thyroid autoantibodies and the autoimmunity between OMG and autoimmune thyroid diseases may be significantly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarizes the clinical features of each case, many of which highlight the difficulties in making a dual diagnosis. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] In prospective and retrospective series of patients with TED, 0.7% to 1.3% will also be diagnosed with MG. 11,47,48 Of patients with coexisting TED and MG, isolated OMG is more common than the generalized form. 49,50 Most MG patients with coexisting TED tend to have a benign course and rarely require treatment beyond symptomatic therapy with AChEIs, but more severe cases requiring intubation and systemic immunotherapy have been reported.…”
Section: Coexisting Omg and Tedmentioning
confidence: 99%
“…We performed a PubMed search in the English literature focusing on publications since 1980. Table 2 summarizes the clinical features of each case, many of which highlight the difficulties in making a dual diagnosis 31‐46 …”
Section: Clinical Presentationmentioning
confidence: 99%